PENGEMBANGAN MEDIA MONOPOLI TEMATIK BERBASIS MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY PADA TEMA INDAHNYA KERAGAMAN DI NEGERIKU UNTUK SISWA KELAS IV SDN 104204 SAMBIREJO TIMUR KAB. DELI SERDANG - Lala Jelita Ananda; Cici Annisa (Universitas Negeri Medan, 2020)
The purpose of this research is to produce a thematic monopoly media based on the two stay two stray cooperative learning model on the theme of 7 the beauty of diversity in my country that is suitable for grade IV students of SDN 104204 Sambirejo Timur on sub-theme 3 the beauty of unity and unity of my learning country 1. The research instrument consisted of observations, interviews and questionnaires. The results showed that the assessment of media experts in stage I by validator 1 received an average score of 4.05 in the good category, and validator 2 received an average score of 4.25 in the good category. While the validation of material experts in stage I by validator 1 gets an average score of 3.50 in the good category, and validator 2 gets an average score of 4.25 in the good category. Then the assessment of the media in stage II obtained by validator 1 gets an average score of 4.50 in the excellent category, and validator 2 gets an average score of 4.70 in the very good category. In the validation of material experts in stage II by validator 1 get an average score of 4.60 categories is very good, and validator 2 get an average score of 4.66, including very good category and worthy of testing without revision. Based on the explanation above, it can be concluded that the thematic monopoly media based on the two stay two stray cooperative learning model on the theme of the beauty of diversity in my country is feasible for learning grade IV SDN 104204 Sambirejo Timur T.A 2019/2020.Keywords: educational game tools, thematic monopoly, grade IV elementary school.